Estimating theoretical stress regime for engineered geothermal energy systems in an arctic community (Kuujjuaq, Canada) - Miranda, Mafalda M.; Raymond, Jasmin; Dezayes, Chrystel (Comptes Rendus. Géoscience)
In remote northern regions, lacking deep geothermal exploratory boreholes, a theoretical approach to provide a first-order estimate of the stress regime seems a useful tool. Literature data was used in this context to evaluate the orientation of the stress components and empirical relationships were applied to calculate their magnitude in a community of Nunavik, northern Quebec. A Monte Carlo-based sensitivity analysis was carried out due to the uncertainty of the input parameters. Mohr–Coulomb friction and slip tendency analyses were additionally undertaken to assess the stress state and potential reactivation of existing fractures. The results highlight how the poor knowledge of the stress field has an important impact on the design and development of engineered geothermal energy systems in the Canadian off-grid community of Kuujjuaq.